Recent Advances in Developing Inhibitors for Hypoxia-Inducible Factor Prolyl Hydroxylases and Their Therapeutic Implications - Kim, So Yeon; Yang, Eun Gyeong (MDPI, 2015)
Hypoxia-inducible factor (HIF) prolyl hydroxylases (PHDs) are members of the 2-oxoglutarate dependent non-heme iron dioxygenases. Due to their physiological roles in regulation of HIF-1 stability, many efforts have been focused on searching for selective PHD inhibitors to control HIF-1 levels for therapeutic applications. In this review, we first describe the structure of PHD2 as a molecular basis for structure-based drug design (SBDD) and various experimental methods developed for measuring PHD activity. We further discuss the current status of the development of PHD inhibitors enabled by combining SBDD approaches with high-throughput screening. Finally, we highlight the clinical implications of small molecule PHD inhibitors.
Keywords: FOCAL CEREBRAL-ISCHEMIA; VHL TUMOR-SUPPRESSOR; FACTOR-I; OXYGEN SENSORS; 4-HYDROXYLASE INHIBITORS; DOMAIN PROTEIN-2; NORMOXIC CELLS; HIF PATHWAY; HIF-1-ALPHA; ASSAY